Neogene Paleomagnetic Study of the Western Baicheng Depression: Implications for the Intensified Deformation of Tian Shan Since the Latest Miocene. Issue 12 (14th December 2018) - Zhang, Zhiliang; Sun, Jimin; Lü, Lixing; Wang, Weitao; Li, Yousheng
Abstract: The fold‐and‐thrust belts in the southern forelands of Tian Shan were tectonically deformed as a result of intracontinental deformation in response to the India‐Asia collision; therefore, they are essential for understanding tectonic evolution and basinward propagation of the Tian Shan Range. Although the reactivation of Tian Shan has long been studied, when and how this deformation was initiated and propagated are still controversial. In this study, we present new paleomagnetic results, anisotropy of magnetic susceptibility, tectonic rotations, and interpretations of subsurface seismic images on the Kalayuergun Structural Belt, western Baicheng Depression. Our new results suggest that the deformation of the Kalayuergun Structural Belt initiated at 5.3 Ma and became young southeasterly, indicating that the deformation reached to the study area in the latest Miocene and propagated basinward progressively since then. The clockwise rotations, about half amounts of which must have been occurred at around 5.3 Ma, can be linked to the activity of the Kalayuergun dextral strike‐slip fault on the western end of the anticline. Combined with previous results around Tian Shan, we suggest that the long range has been subjected to an episode of intensified tectonic deformation since the latest Miocene, which was caused by the accelerated northward motion of the Tarim Block and Pamir in response to the India‐Asia collision. Key Points: Neogene magnetostratigraphy and seismic images suggest that the deformation initiated at 5.3 Ma and then propagated basinward progressively The activity of the Kalayuergun dextral strike‐slip fault dominated the rotations of the late Miocene sediments The intensified deformation since 5.3 Ma along Tian Shan resulted from the accelerated northward motion of the Tarim Block and Pamir